"Avaliar através do olhar do outro": a avaliação na educação infantil em tempos de pandemia - LOPES, Jodelma de Campos (2023)
This article discusses how the assessment was carried out in Early Childhood Education during the Covid-19 Pandemic through remote teaching and the resumption of face-to-face classes, at the Criança Feliz Educational Center, with reports from two teachers through an open questionnaire. We used a bibliographic survey on the conception of childhood, evaluation, evaluation in Early Childhood Education and a brief report on the Covid-19 Pandemic, which allowed us to analyze, critically and reflectively emphasize the teachers' speeches.